Electrocatalytic oxygen evolution and antiproliferative activity of Co(III) complexes stabilized by in situ generated bis(5‐furan/phenyl‐1, 2, 4‐triazole)‐3‐sulfinamide. (26th October 2021) - Bharty, Manoj Kumar; Singh, Aarti; Bharati, Pooja; Pandey, Shivendra Kumar; Singh, Devesh Kumar; Ganesan, Vellaichamy; Verma, Praveen Kumar; Acharya, Arvind; Bharti, Akhilesh; Butcher, Ray J.
Abstract : Electrocatalytic water oxidation by transition metal complexes is an emerging area of research. Here, two cobalt(III) complexes [Co(ftsm)NH3 ( o ‐phen)]·H2 O (1 ) ftsm = bis (5‐furan‐1, 2, 4‐triazole)‐3‐sulfinamide and [Co(ptsm)NH3 ( o ‐phen)]·CH3 OH (2 ) ptsm = bis (5‐phenyl‐1, 2, 4‐triazole)‐3‐sulfinamide were synthesized and characterized by various spectroscopic and X‐ray crystallography techniques. Complexes 1 and 2 were found to have admirable electrocatalytic activity towards oxygen evolution reaction (OER). The Tafel slope values for GC/Nf‐Complex‐2 and GC/RuO2 were 53 and 60 mV/dec, respectively. Consequently, complex 2 possesses a better water oxidation response than standard material RuO2 . The ligands Haftt, Haptt, o ‐phen, and complexes 1 and 2 were also tested for their cytotoxicity against Dalton's lymphoma (DL) cells employing MTT assay and found to have significant cytotoxicity. The IC50 values of Haftt, Haptt, mixed ligands Haftt + o ‐phen and Haptt + o ‐phen, and complexes 1 and 2 against DL cells were found to be 150, 400, 200, 450, 80, and 5 μM, respectively. The complexes were found to have minimal effect on normal cells. The remarkable IC50 value for complex 2 shows that it can be utilized as a potential anticancer agent against DL cells. Abstract : Electrocatalytic water oxidation by two novel Co(III) complexes is reported in this work. Various electrocatalytic parameters of these complexes were also compared with previously reported complexes. Both the complexes have shown admirable electrocatalytic activity for oxygen evolution. The antiproliferative effect of ligands, salt, and complexes against DL cells was also studied, and result shows complexes have remarkable antitumor activity in comparison with free ligand or metal salt.